2019
DOI: 10.3389/fendo.2019.00790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Five-Gene Signature and Establishment of a Prognostic Nomogram to Predict Progression-Free Interval of Papillary Thyroid Carcinoma

Abstract: Background: The incidence of papillary thyroid carcinoma (PTC) is high and increasing worldwide. Although prognosis is relatively good, it is important to select the minority of patients with poorer prognosis to avoid side effects associated with unnecessary over-treatment in low-risk patients; this requires accurate prognostic predictions.Materials and Methods: Six PTC expression datasets were obtained from the gene expression omnibus (GEO) database. Level 3 mRNA expression and clinicopathological data were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…FXYD6 is known as a speci c modulator of Na, K-ATPase, and is expressed in multiple epithelial cells of the inner ear [52]. In accordance with the current study, FXYD6 was previously identi ed to be downregulated in PTC and was associated with poor prognosis [53]. CLCNKB is a voltage-gated chloride channel participating in the regulation of cell volume, membrane potential stabilization, signal transduction, and transepithelial transport [54].…”
Section: Discussionsupporting
confidence: 83%
“…FXYD6 is known as a speci c modulator of Na, K-ATPase, and is expressed in multiple epithelial cells of the inner ear [52]. In accordance with the current study, FXYD6 was previously identi ed to be downregulated in PTC and was associated with poor prognosis [53]. CLCNKB is a voltage-gated chloride channel participating in the regulation of cell volume, membrane potential stabilization, signal transduction, and transepithelial transport [54].…”
Section: Discussionsupporting
confidence: 83%
“…Keiko et al show that loss of GGCT leads to autophagy in breast and prostate cancer cells in vitro (40). FXYD6 is also a new biomarker to predict the progression-free interval of PTC (41), and FN1 was positively related to the pathologic stage of PTC patients (42).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PTC in the high-risk group may demonstrate poor clinical outcomes, including aggressive tumor behavior, disease recurrence and disease-specific mortality; therefore, treatment strategies such as prophylactic central neck dissection, radioactive iodine therapy and close long-term follow-up may be applied. Wu et al (46) identified DEGs related to the progression-free interval (PFI) and applied lasso Cox regression to establish a prognostic gene signature which could predict the PFI of PTC. Similar multi-mRNA prognostic models have also been constructed in other tumor types.…”
Section: Discussionmentioning
confidence: 99%